Modelling of assembly line balancing with energy consumption - Ariff Nijay, Ramli; Mohd Fadzil Faisae, Ab Rashid (AIP Publishing, 2023)
One of the most gravitate issues in the world is energy usage. As the largest consumer in terms of energy usage, the manufacturing sector had introduced a lot of approaches to decrease their energy utilization. As the energy usage issue becomes more prominent, researchers had applied the Assembly Line Balancing (ALB) optimization that considers energy utilization as one of their efforts in reducing energy consumption. This paper discusses the related papers done by researchers, demonstrates the ALB model developed with electrical energy consideration by the application of the Matlab simulation and its validation through the manual hand calculation. The ALB with Energy Consideration (ALB-EC) was modelled into a mathematical model that could be used in solving the Simple Assembly Line Balancing Problem (SALBP), with the application of the Matlab application. The Particle Swarm Optimization (PSO) algorithm was applied and the model was tested by using three problems which consist of each of a small, medium, and large-sized test problem. Based on the finding, we could achieve the same results on the computational method along with the manual hand calculation for the evaluated total energy and objective functions. Besides, the advantages and limitations of the proposed model were also discussed in this paper. Through the application of this study, it could contribute to the reduction of electrical energy usage in the production line, which can reduce the overall energy usage CO2 gas production and prevent climate change.